Patents to products: Product innovation and firm dynamics - David Argente; Salomé Baslandze; Douglas Hanley; Sara Moreira (Federal Reserve Bank of Atlanta, 2020)
We study the relationship between patents and actual product innovation in the market, and how this relationship varies with firms' market share. We use textual analysis to create a new data set that links patents to products of firms in the consumer goods sector. We find that patent filings are positively associated with subsequent product innovation by firms, but at least half of product innovation and growth comes from firms that never patent. We also find that market leaders use patents differently from followers. Market leaders have lower product innovation rates, though they rely on patents more. Patents of market leaders relate to higher future sales above and beyond their effect on product innovation, and these patents are associated with declining product introduction on the part of competitors, which is consistent with the notion that market leaders use their patents to limit competition. We then use a model to analyze the firms' patenting and product innovation decisions. We show that the private value of a patent is particularly high for large firms as patents protect large market shares of existing products.
Keywords: O3; O4; 330; product innovation; patents; creative destruction; growth; productivity; patent value